Differences in microRNA-29 and Pro-fibrotic Gene Expression in Mouse and Human Hypertrophic Cardiomyopathy - Liu, Yamin; Afzal, Junaid; Vakrou, Styliani; Greenland, Gabriela V.; Talbot, C. Conover; Hebl, Virginia B.; Guan, Yufan; Karmali, Rehan; Tardiff, Jil C.; Leinwand, Leslie A.; Olgin, Jeffrey E.; Das, Samarjit; et al. (Frontiers in Cardiovascular Medicine, 2019)
Background: Hypertrophic cardiomyopathy (HCM) is characterized by myocyte hypertrophy and fibrosis. Studies in 2 mouse models (R92W-TnT/R403Q-MyHC) at early HCM stage revealed upregulation of endothelin (ET1) signaling in both mutants, but TGFβ signaling only in TnT mutants. Dysregulation of miR29 expression has been implicated in cardiac fibrosis. But it is unknown whether expression of miR29a/b/c and profibrotic genes is commonly regulated in mouse and human HCM. Methods: In order to understand mechanisms underlying fibrosis in HCM, and examine similarities/differences in expression of miR29a/b/c and several profibrotic genes in mouse and human HCM, we performed parallel studies in rat cardiac myocyte/fibroblast cultures, examined gene expression in 2 mouse models of (non-obstructive) HCM (R92W-TnT, R403Q-MyHC)/controls at early (5wks) and established (24wks) disease stage, and analyzed publicly available mRNA/miRNA expression data from obstructive-HCM patients undergoing septal myectomy/controls (unused donor hearts). Results: Myocyte cultures: ET1 increased superoxide/H2O2, stimulated TGFβ expression/secretion and suppressed miR29a expression in myocytes. The effect of ET1 on miR29 and TGFβ expression/secretion was antagonized by N-acetyl-cysteine, a reactive oxygen species scavenger. Fibroblast cultures: ET1 had no effect on pro-fibrotic gene expression in fibroblasts. TGFβ1/TGFβ2 suppressed miR29a and increased collagen expression, which was abolished by miR29a overexpression. Mouse and human HCM: Expression of miR29a/b/c was lower, and TGFB1/collagen gene expression was higher in TnT mutant-LV at 5&24 weeks; no difference was observed in expression of these genes in MyHC mutant-LV and in human myectomy tissue. TGFB2 expression was higher in LV of both mutant mice and human myectomy tissue. ACE2, a negative regulator of the renin-angiotensin-aldosterone system, was the most upregulated transcript in human myectomy tissue. Pathway analysis predicted upregulation of the anti-hypertrophic/anti-fibrotic liver X receptor/retinoid X receptor (LXR/RXR) pathway only in human myectomy tissue. Conclusions: Our in vitro studies suggest that activation of ET1 signaling in cardiac myocytes increases reactive oxygen species and stimulates TGFβ secretion, which downregulates miR29a and increases collagen in fibroblasts, thus contributing to fibrosis. Our gene expression studies in mouse and human HCM reveal allele-specific differences in miR29 family/profibrotic gene expression in mouse HCM, and activation of anti-hypertrophic/anti-fibrotic genes and pathways in human HCM.